Modeling of copper ions adsorption onto oxidative-modified activated carbons - LM Grishchenko; VE Diyuk; OP Konoplitska; VV Lisnyak; RT Maryichuk (Adsorption Science & Technology, 2017)
In this work, the adsorption of copper ions onto activated carbons that oxidatively modified with H 2 O 2 and HNO 3 was studied. The prepared sorbents with the surface area of 275–780 m 2 /g contain 0.53–3.77 mmol/g of oxygen-containing groups. It was found that the oxidized activated carbon effectively adsorbs Cu 2+ ions from aqueous solutions. For the most efficient activated carbon–HNO 3 –30 sorbent, the percentage removal of copper ions from solutions of varying concentration is high. In the concentration range from 1.5 to 6 × 10 −4  M of Cu 2+ , it reaches >55%. At the concentrations lower than 1.5 × 10 −4  M, the expected removal is above 80%. The experimental equilibrium adsorption data were modeled with 2- and 3-parameter isotherms. The analysis of adsorption modeling results accounting for the surface heterogeneity effect was provided. The data fit well to the Dubinin–Radushkevich model. Presumably, the complexation of Cu 2+ with oxygen-containing groups passes within micropores. We found the correlation between the sorption capacity for Cu 2+ and the concentration of surface groups. The presence of the carboxyl, anhydride, and lactone groups make a major impact on the adsorption.